Building the Future of Education with Curriculum Innovation Freedom to Learn in the Era of Society 5.0 - Sappaile, Baso Intang; Wiliyanti, Vandan; Mustajab, Wahyu; Prayitno, Hadi; Panglipur, Indah Rahayu (International Journal of Educational Research Excellence (IJERE), 2024)
The Merdeka Curriculum constitutes an innovative educational approach that responds to evolving societal and technological demands within the Society 5.0 framework. This study conducted a comprehensive review of existing literature to gain insight into the Merdeka Curriculum's underlying philosophy and assess its contribution to basic education. The findings indicate that the Merdeka Curriculum is designed to foster the development of essential 21st-century skills required in the era of the industrial revolution 4.0. To ensure effective implementation, it is necessary to effect changes in the educational paradigm, develop teacher competencies, and garner support from various stakeholders. The Merdeka Curriculum presents an invaluable opportunity to cultivate students with the requisite attributes to thrive in an era of accelerating technological and social change. This literature study offers a nuanced understanding of the Merdeka Curriculum in the context of basic education that is pertinent to the challenges of the present moment.